Analisis Faktor-Faktor Yang Mempengaruhi Pengelolaan Aset di Institut Pemerintahan Dalam Negeri Kampus Papua - Juliessi Paranga (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2020)
The purpose of this study is to investigate the assets management in the Papua Campus of Institut Pemerintahan Dalam Negeri (IPDN). The research also wants to reveal how the influence of Legal Audit, Human Resources and Leadership Commitments on Optimizing Asset Management. We surveyed on this  Campus by selecting a sample of 30 respondents. We empirically tested our hypothesis using Multiple Regression Analysis. The results show that the assets management on this Campus is proper and running under the appropriate statutes. Still, there are needs for more advance and thought in the assets administration, utilization and supervision. Legal audit proved to have a positive but not significant effect on asset management. It means that the audit does not guarantee asset optimization. Human resources and leadership commitments have a positive and significant impact on asset management, reflects that if human resources and leadership commitments are getting more robust, asset management will also be more trustworthy.